Self-generated coping strategies among Muslim athletes during Ramadan fasting - Roy, J.; Hwa, O. C.; Singh, R.; Aziz, A. R.; Jin, C. W. (Journal of Sports Science & Medicine, 2011)
The study explored the self-generated coping strategies employed by Muslim athletes from South East Asian region during the Ramadan fasting month. Sixty-five National elite Muslim athletes responded to an open-ended question on coping strategies employed during Ramadan fasting. Inductive content analysis identified five general dimensions from 54 meaning units which were abstracted into 14 first-order themes and 10 second order themes. The general dimension included four problem-focused coping: training modifications, dietary habits, psychological, rest and recovery, and one emotion-focused coping i.e., self- control. The coping strategies employed were diverse and dynamic in nature and no specific pattern was evident. The most frequently employed strategies were associated with training and dietary habits. Emotion focused coping was the least frequently used by the athletes.